Sexual aggression against males: Differences between acts by males and females – Results from the German Health and Sexuality Survey (GeSiD). (July 2021) - Tozdan, Safiye; Brunner, Franziska; Pietras, Laura; Wiessner, Christian; Briken, Peer
Abstract: Background: Current research examining sexual aggression against males is rare and representative studies often do not sufficiently differentiate between male and female affected persons, male and female offending person, as well as between different types of sexual aggression. Objective: We investigated the prevalence of sexual aggression against males perpetrated by males and females distinguished by the type of sexual aggression and examined differences between sexual aggression against males committed by males and females in characteristics of the sexual aggression. Participants and Setting: We examined representative self-report data collected in the German Health and Sexuality Survey (GeSiD; n = 4, 955). A total of 305 male participants (12.3 % of all male participants) experienced at least one incident of sexual aggression. Method: We investigated differences between characteristics of male- and female-perpetrated sexual aggression against males in cases of (1) sexual aggression against minors by adults, (2) sexual aggression among minors/peers, and (3) sexual aggression among adults. Characteristics of sexual aggression included were frequency, relation of accused person, disclosure, participant's age at first incident, and accused person's age at first incident. Results: Our results revealed that the proportion of sexual aggression by females against males is rather low in cases of sexual aggression against minors by adults (9 %) compared with sexual aggression among minors/peers (56 %) and among adults (52 %). Although the majority of characteristics of sexual aggression were similar, some differences between male- and female-perpetrated sexual aggression were found. Conclusions: Sexual aggression against males appears to be an under-researched phenomenon, especially when it is perpetrated by a female person. More research on sexual aggression against males as well as on the differences between male- and female-perpetrated sexual aggression is therefore considered necessary.